(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the fundamental characteristics of modular training as an innovative approach to education and professional development. Modular training is distinguished by its flexibility, learner-centered design, and focus on mastering discrete units of knowledge and skills. The study explores the structure, advantages, and implementation challenges of modular training systems across various educational contexts. Special attention is given to how modular training facilitates personalized learning paths, promotes autonomy, and supports competency-based education. The article also discusses practical recommendations for designing effective modular training programs that align with modern educational standards and meet the evolving needs of learners and organizations.